Associations of 24-h Movement Behaviors With Incidence of Cardiovascular Risk Factors: The Finnish Retirement and Aging Study - Suorsa, Kristin; Leskinen, Tuija; Pasanen, Jesse; Pentti, Jaana; Vahtera, Jussi; Stenholm, Sari (WILEY, 2025)
Low physical activity, high sedentary time (SED), and inadequate sleep increase cardiovascular disease risk, but the codependency between these 24-h movement behaviors has often been neglected. This study examined associations between 24-h movement behaviors and incidence of cardiovascular risk factors. The study included 866 adults (mean age 62.4 years, SD 1.1) from the Finnish Retirement and Aging study who participated in wrist-accelerometry measurements between 2014 and 2018. Incident register-based cardiovascular risk factors including hypertension, dyslipidemia, type 2 diabetes, and questionnaire-based obesity were followed up over on average 3-year follow-up. Compositional Cox regression models were adjusted for age, sex, occupation, smoking, and heavy alcohol consumption. We recorded 84 (17%) new cases of hypertension, 66 (9%) dyslipidemia, 28 (3%) type 2 diabetes, 43 (6%) obesity, and 94 (26%) any of these cardiovascular risk factors. Compared to mean composition (7.8 h sleep, 11.0 h SED, 4.2 h light physical activity [LPA], 60 min moderate-to-vigorous physical activity [MVPA]), having 10 min more MVPA at the cost of other behaviors was associated with 5%-7% risk reduction in hypertension, 10%-13% in obesity, and 6%-7% in any cardiovascular risk factor. Among the least active (sleep 7.9 h, SED 12.1 h, LPA 3.6 h, MVPA 24 min), the risk reductions were nearly twofold. In conclusion, when accounting the interdependence of movement behaviors, MVPA associated with highest risk reduction in hypertension and obesity, especially among the least active participants. This suggests that even a small increase in daily MVPA could help prevent development of cardiovascular risk factors.